Influence of Vessel Configuration and Size of Vessel Wall Based on the Numerical Analysis of Polar Solvent Heated by Microwave - Shu, J.; Yang, X.Q.; Huang, K.M.; Jia, G.Z.; Li, K.; Zhang, J.L. (Asian Journal of Chemistry, 2012)
The choice of vessel is vital for heating polar solvent. In this paper, water at silicon carbide or glass vessel with three different configurations and size of vessel wall were heated by microwave. The uniformities of temperature were analyzed using COMSOL Multiphysics under different configurations and size of vessel wall during microwave heating. It was concluded that the temperature uniformities were influenced by the parameters of different configurations and size of vessel wall, when the improvement in temperature uniformity is not obvious for one configuration, it can be significantly improved by changing to another specific configuration and size of vessel wall.